Planejamento sucessório, governança corporativa e inovaçã: uma investigação das relações com o desempenho organizacional em empresas familiares - Ortega, Vera Lucia Robles (2018)
This study aimed to investigate the relationships between succession planning, corporate governance, innovation and organizational performance in family firms. The research was conducted under the quantitative approach, using primary data, classified as an exploratory, ex-post-facto, descriptive, cross-sectional, survey, field environment and actual routine. The sample consisted of 56 family companies aged 30 years or more in Curitiba. Data were analyzed by means of the following tests: a) descriptive statistics, b) correlation test, c) multiple linear regression test and d) moderation test. In the theoretical frame of reference was contextualized the familiar company - origin and history in Brazil, concepts and their relevance. For the constructs succession planning, corporate governance, innovation and organizational performance, the research went beyond the boundary of concepts, to understand them in the vision of a family business. For the study of family business and family succession, the three circles of Gersick (1993), which describes the family business system with three independent, but overlapping subsystems: management, property, and family, were considered. "[...] succession is not one situation, but several" is possible to go beyond, taking up the variables of time, process and preparation. Corporate governance is embedded in research, by the ability to implement mechanisms to guide and drive the succession process, contributing to the balance and perpetuation of family business. Rossetti and Andrade (2014) affirm that one of the most important dimensions of corporate governance is the values that support it, tying high management conceptions, practices and processes. Understanding that innovation is required for company longevity, a study of the balance of exploration and exploitation activities presented by March (1991) was added. In order to evaluate organizational performance as a control of strategies defined by family companies, a multidimensional model of the performance concept was used: economic, financial, market and operational (Matitz and Bulgacov, 2011). The results of the research demonstrated that the hypotheses proposed in this study were refuted when considering the multidimensional concept of organizational performance. However, the same models proposed, using a one-dimensional concept of organizational performance, in particular, the total value of sales, found results of statistical significance. For the main hypothesis of this study, the regression test demonstrated an explained variance of 35.4% of the total sales value. One of the contributions of this research was to expand the analysis of the hypotheses to understand the relationship of the proposed models with the one-dimensional concept of performance. Its best performance occurred in the moderation test between succession planning maturity and organizational ambidexterity degree, provoking interaction effect, with an explained variance of 43.74%, in total sales revenue. Another contribution of this study was to test alternative models between the studied constructs and to find significant moderating effects when considered a confidence interval of 0.10.